El museo de la colegiata de Santa María de Calatayud - Alegre Arbués, Jesús Fernando (Artigrama, 2014)
ResumenEl Museo de la colegiata de Santa María de Calatayud, ubicado en el claustro mudéjar, fue inaugurado en 2006. Ocupa las naves claustrales y las salas capitulares vieja y nueva, además de una de las crujías del claustro alto, exponiéndose parte del rico patrimonio artístico de la colegiata: pintura, escultura, orfebrería y textiles.AbstractThe Museum of the Church of Santa María de Calatayud, located in the Mudejar cloister, was opened in 2006. It occupies the cloistered aisles and the old and new chapter houses, plus one of the bays of the upper cloister, exposing part of the rich artistic heritage of the collegiate painting, sculpture, metalwork and textiles.KeywordsMuseo de Santa María de Calatayud, cloister, painting, sculpture, metalwork and textiles.